Hundred years of the Bauddha Dharmankur Sabha, the Bengal Buddhist Association, 1892-1992 - Chowdhury, Hemendu Bikash; Bauddha Dharmankur Sabha (Calcutta, India : The Sabha, 1992)
Centenary volume of the Bauddha Dharmankur Sabha; comprises contributed articles chiefly on various aspects of Buddhism.
Editor: Hemendu Bikash Chowdhury.
Includes bibliographical references.
English and Bengali.
Keywords: Buddhism